Relationship between Artificial Intelligence and Students’ Learning Strategies at Secondary Level - Kausar, Fahd Naveed; Bahoo, Rabia; Qaisara, Rani; Waseem, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The objective of the study was to identify the level of AI and students’ learning strategies, and to find the relationship between AI and students’ learning strategies at secondary level. Artificial Intelligence is reshaping students' learning strategies by providing personalized content, immediate feedback, and data-driven insights that enhance engagement and comprehension. However, while AI promotes self-regulated learning and collaboration, it also requires careful balance to preserve essential human interaction in education. A quantitative and descriptive method is used in the study. The majority of participants were in the secondary school district of Sheikhupura. A questionnaire served as this study's primary research tool. The validity of the questionnaire was found through experts’ opinions and reliability through pilot testing. Descriptive and inferential statistics was used. The findings of the study revealed that there was highly significant relationship between AI and students’ learning strategies at secondary level.